2015
DOI: 10.5493/wjem.v5.i4.218
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic antioxidant system in vascular inflammation and coronary artery disease

Abstract: In biological systems there is a balance between the production and neutralization of reactive oxygen species (ROS). This balance is maintained by the presence of natural antioxidants and antioxidant enzymes such as superoxide dismutase (SOD), catalase and glutathione peroxidase. The enhancement of lipid peroxidation or the decrease of antioxidant protection present in metabolic diseases or bad lifestyle can induce endothelial dysfunction and atherosclerosis. Clinical studies have shown that oxidative stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 45 publications
3
83
1
2
Order By: Relevance
“…Although some studies have demonstrated an association between salivary markers of oxidative stress and periodontal status, no significant difference was observed in the salivary concentration of TBARSs among the groups in the present study . It is possible to suggest that this result is because of a compensatory effect of the antioxidant capacity of saliva, which involves the action of different mechanisms, such as antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase, which are involved in the neutralization of free radicals …”
Section: Discussioncontrasting
confidence: 83%
“…Although some studies have demonstrated an association between salivary markers of oxidative stress and periodontal status, no significant difference was observed in the salivary concentration of TBARSs among the groups in the present study . It is possible to suggest that this result is because of a compensatory effect of the antioxidant capacity of saliva, which involves the action of different mechanisms, such as antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase, which are involved in the neutralization of free radicals …”
Section: Discussioncontrasting
confidence: 83%
“…Similar results have been reported in studies measuring salivary and serum levels of antioxidants (peroxidase, superoxide dismutase, salivary total antioxidant status) in patients with type 1 diabetes mellitus. Increased antioxidant levels have been observed in these patients, indicating a compensation of the antioxidant systems against oxidative stress (36).…”
Section: Discussionmentioning
confidence: 99%
“…SOD plays an important role in scavenging free radicals, so the SOD level in organization always is considered as the main indicator of scavenging free radical ability. (31) The present research shows that HSYA and Danhong Injection markedly increased the SOD activity, while daiclzein, HSYA and Danhong Injection significantly decreased the MDA level.…”
Section: Discussionmentioning
confidence: 83%